2014
DOI: 10.1111/sltb.12109
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does the Reporting Behavior of the Media Regarding a Celebrity Suicide Influence Subsequent Suicides in South Korea?

Abstract: This study investigated the nature of media coverage of a national entertainer's suicide and its impact on subsequent suicides. After the celebrity suicide, the number of suicide-related articles reported surged around 80 times in the week after the suicide compared with the week prior. Many articles (37.1%) violated several critical items on the World Health Organization suicide reporting guidelines, like containing a detailed suicide method. Most gender and age subgroups were at significantly higher risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
0
30
1
4
Order By: Relevance
“…This pattern of imitative suicide is called the Werther effect (Phillips 1974), named after the main character in Goethe's 1774 novel The Sorrows of Young Werther, whose fictional suicide induced an increase in real suicides at the time in Europe (Stack 2003). Prior research has found empirical support for the Werther effect with regard to celebrity suicides (Lee et al 2014;Niederkrotenthaler et al 2012;Stack 1987;1990;2003;Wasserman 1984;Yang et al 2013;Yip et al 2006). Anomie and imitation are presented as the main explanatory mechanisms of the Werther effect.…”
Section: Anomie or Imitation? The Werther Effect Of Celebrity Suicidementioning
confidence: 87%
See 2 more Smart Citations
“…This pattern of imitative suicide is called the Werther effect (Phillips 1974), named after the main character in Goethe's 1774 novel The Sorrows of Young Werther, whose fictional suicide induced an increase in real suicides at the time in Europe (Stack 2003). Prior research has found empirical support for the Werther effect with regard to celebrity suicides (Lee et al 2014;Niederkrotenthaler et al 2012;Stack 1987;1990;2003;Wasserman 1984;Yang et al 2013;Yip et al 2006). Anomie and imitation are presented as the main explanatory mechanisms of the Werther effect.…”
Section: Anomie or Imitation? The Werther Effect Of Celebrity Suicidementioning
confidence: 87%
“…In 2008, a famous South Korean actress committed suicide, and her death led to a rise in the country's suicide rate in the following months (Lee et al 2014). This pattern of imitative suicide is called the Werther effect (Phillips 1974), named after the main character in Goethe's 1774 novel The Sorrows of Young Werther, whose fictional suicide induced an increase in real suicides at the time in Europe (Stack 2003).…”
Section: Anomie or Imitation? The Werther Effect Of Celebrity Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…M edia reports on suicide deaths are related to increases in suicidal behavior in the general population. [1][2][3][4] For instance, Kim conducted a content analysis of 3,412 suicide lifeline calls in South Korea and found that media reports of others' suicide deaths, including celebrity suicides, impacted the details of the individuals' own suicide plans. Specifically, publicized suicide deaths provided ideas for what method(s) to use and places where to make an attempt.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about iatrogenic effects of media reporting have been examined in more than 50 observational and naturalistic studies across nations and cultures, some of which suggest that media coverage of suicide and subsequent population suicide rates are correlated (Sisak & Varnik, 2012). Results of a meta-analysis of 10 international, population-based studies further suggest that suicide rates increased by .26 per 100,000 during the month immediately following a celebrity suicide, with larger increases being associated with the national prominence of the celebrity (Lee, Lee, Hwang, & Stack, 2014;Niederkrotenthaler et al, 2012). That being said, according to reviews considering the findings across studies, support for a "copycat" effect is infrequent and limited to specific contexts (e.g., Stack, 2003Stack, , 2005.…”
mentioning
confidence: 99%